2014
DOI: 10.1186/1749-8090-9-45
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of video-assisted thoracoscopic surgery lung biopsies in patients with interstitial lung disease: a retrospective study of 66 patients

Abstract: BackgroundDiagnosing a specific type of Interstitial Lung Disease (ILD) is a challenging process and often necessitates that a Video-assisted Thoracoscopic Surgery (VATS) Lung Biopsy be performed. By analysing the proportion of patients who have their treatment changed after undergoing a VATS lung biopsy, this study aimed to determine the utility of performing this procedure in patients with ILD.MethodsThe clinical data from sixty-six patients with suspected ILD, who underwent VATS lung biopsies at the New Roy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
5
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 31 publications
4
32
5
2
Order By: Relevance
“…Our overall figure of 2.4% 30-day mortality is similar to that reported by CARRILLO et al [21] in the next largest series, of 722 patients in Mexico from 1986 to 1990, and also SIGURDSSON et al [20] in a smaller nationwide series from Iceland from 1986 to 2007. It is slightly higher than the 2.1% estimate for VATS procedures from a systematic review by NGUYEN and MEYER [7] and the 1.5% estimate from a recent case series in Edinburgh, UK [4], but lower than a previous summary estimate reported by KREIDER et al [6] (4.5%) (although this included studies with varying mortality end-points). Although comparison of mortality figures depends on case mix, end-points and procedure types, this consistency supports our estimates, and the comparison to mortality post-lobectomy is not insignificant [16].…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Our overall figure of 2.4% 30-day mortality is similar to that reported by CARRILLO et al [21] in the next largest series, of 722 patients in Mexico from 1986 to 1990, and also SIGURDSSON et al [20] in a smaller nationwide series from Iceland from 1986 to 2007. It is slightly higher than the 2.1% estimate for VATS procedures from a systematic review by NGUYEN and MEYER [7] and the 1.5% estimate from a recent case series in Edinburgh, UK [4], but lower than a previous summary estimate reported by KREIDER et al [6] (4.5%) (although this included studies with varying mortality end-points). Although comparison of mortality figures depends on case mix, end-points and procedure types, this consistency supports our estimates, and the comparison to mortality post-lobectomy is not insignificant [16].…”
Section: Discussioncontrasting
confidence: 46%
“…Case series have reported 30-day mortality rates of around 1.5-4.5%, although these may be biased by careful case selection or local expertise and are not necessarily generalisable to other centres [4][5][6][7]. Other case series note much higher mortality rates [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…6,[21][22][23][24][25] Moreover, 8 studies evaluated the frequency in which the biopsy changed the treatment algorithm, ranging from 42% to 90%. 7,8,10,15,18,20,22,24 The change was driven by specific diagnosis in 6 studies 8,15,18,20,22,24 and was not necessarily related to specific diagnosis in 2 studies. 7,10 A total of 17 studies reported biopsy sites; 11 studies were guided by computed tomography without special preference.…”
Section: Diagnostic Yieldmentioning
confidence: 99%
“…This study based on epidemiologic data adds to previous accumulating evidence from case series [13][14][15][16][17][18] indicating that the risk of surgical lung biopsy is clinically significant, even if it is lower than that in older series with probably less careful selection of cases [19,20]. As emphasised by the authors [11], mortality after a surgical lung biopsy can be compared, for example, to that of lobectomy for lung cancer (2.3%) [21], a therapeutic, not diagnostic, procedure.…”
mentioning
confidence: 98%